2001
DOI: 10.1111/j.1151-2916.2001.tb00951.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Matrix Cracks on the Thermal Diffusivity of a Fiber‐Reinforced Ceramic Composite

Abstract: Effects of matrix cracks and the attendant interface debonding and sliding on both the longitudinal and the transverse thermal diffusivities of a unidirectional Nicalon/MAS composite are investigated. The diffusivity measurements are made in situ during tensile testing using a phase-sensitive photothermal technique. The contribution to the longitudinal thermal resistance from each of the cracks is determined from the longitudinal diffusivity along with measurements of crack density. By combining the transverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 14 publications
2
12
0
Order By: Relevance
“…The effect of distributed porosity and voids is analyzed in “”; as shown there, the diffusivity decreases nearly linearly with the CMC volume fraction (). In many situations, microscopic matrix cracks are aligned in the through‐thickness direction 19 . Therefore, the measurement of through‐thickness thermal diffusivity may not be considered sensitive to these cracks.…”
Section: Thermal Diffusivity Characterization Of Cmc Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of distributed porosity and voids is analyzed in “”; as shown there, the diffusivity decreases nearly linearly with the CMC volume fraction (). In many situations, microscopic matrix cracks are aligned in the through‐thickness direction 19 . Therefore, the measurement of through‐thickness thermal diffusivity may not be considered sensitive to these cracks.…”
Section: Thermal Diffusivity Characterization Of Cmc Materialsmentioning
confidence: 99%
“…However, these cracks normally have lateral extensions, and most importantly, their presence would cause debonding at the matrix/fiber interface once the component is stressed. The debonded interface will impede heat transfer through the interface, and coupled with the large volume fraction of the fibers, interface debonding may considerably reduce thermal diffusivity in the thickness direction 19 . Therefore, thermal diffusivity imaging may still be able to determine the distribution of microscopic cracks and interface debonding.…”
Section: Thermal Diffusivity Characterization Of Cmc Materialsmentioning
confidence: 99%
“…Crack opening displacement (COD) is a function of the applied stress. While CODs can be calculated, most models consider unidirectional reinforcement and require constituent parameters, like interfacial shear stress, that are difficult to measure and are often approximated from other measurements. Direct experimental measurements of COD values are largely unavailable with references being the exceptions.…”
Section: Introductionmentioning
confidence: 99%
“…The latter damage mode is the focus of the present paper; a study of the role of multiple matrix cracks on the in-plane properties is reported elsewhere. 5 To further motivate the current work, it is useful to consider the problem of a thin CMC plate that contains a long delamination crack along the midplane and is subject to a steady-state temperature difference ⌬T between the two surfaces of the plate. The resulting energy release rate for the crack (G) is given by 6 G ϭ EA͑␣⌬T͒ 2 32͑1 ϩ b͒ 2 (1) where E is the in-plane modulus and A is the plate thickness.…”
Section: Introductionmentioning
confidence: 99%